2014
DOI: 10.1007/s11033-014-3830-1
|View full text |Cite
|
Sign up to set email alerts
|

The biological effects of hsa-miR-1908 in human adipocytes

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs involved in the regulation of gene expression. MiR-1908 is a recently identified miRNA that is highly expressed in human adipocytes. However, it is not known what role of miR-1908 is involved in the regulation of human adipocytes. In this study, we demonstrate that the level of miR-1908 increases during the adipogenesis of human multipotent adipose-derived stem (hMADS) cells and human preadipocytes-visceral. Overexpression of miR-1908 in hMADS cells inhibited adipog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Human pre-adipocytes from visceral (omental) adipose were purchased from ScienCell Research Laboratories (Carlsbad, CA, USA). Pre-adipocytes were maintained and induced to differentiate as previously described ( 23 ). Briefly, pre-adipocyte differentiation medium (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Human pre-adipocytes from visceral (omental) adipose were purchased from ScienCell Research Laboratories (Carlsbad, CA, USA). Pre-adipocytes were maintained and induced to differentiate as previously described ( 23 ). Briefly, pre-adipocyte differentiation medium (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ASCs have served as a tool to investigate the role of different genes associated with adipocyte metabolism [ 99 , 100 ]. Finally, ASCs have also been used for the study of miRNAs [ 1 , 101 ] and browning, because they are capable of converting from white to brown adipocytes [ 102 ], which enables the study of the differential effect of certain molecules in white and brown adipogenesis such as p53 [ 103 ].…”
Section: Human Cell Modelsmentioning
confidence: 99%
“…Yu et al [13] demonstrated that peroxisome proliferator activated receptor-γ (PPAR-γ) agonist stimulation has in the subcutaneous and visceral fat depots distinct but overlapping effects on the expression of miRNAs that target the transforming growth factor-β (TGF-β), insulin and Wnt/β-catenin signaling pathways with key roles in the control of adipogenesis. Moreover, in vitro experiments with preadipocyte/adipocyte cultures have provided evidence for functional roles of a number of miRNAs in adipogenesis: miR-103, miR-320, and miR-1908 enhance adipogenesis while miR-146 and miR-194 decrease adipocyte differentiation [9,[14][15][16][17][18]. Of note, correlation was shown between dysregulation of miRNAs targeting white adipose tissue adipocytokine expression and non-alcoholic steatohepatitis [11], consistent with the hypothesis that adipocytokines regulated by miRNAs and secreted by adipose tissue impact the pathogenesis of non-alcoholic fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%